2021
DOI: 10.3389/fevo.2021.636279
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Leads to a Reduction in Symbiotic Derived Cnidarian Biodiversity on Coral Reefs

Abstract: Symbiotic relationships enable partners to thrive and survive in habitats where they would either not be as successful, or potentially not exist, without the symbiosis. The coral reef ecosystem, and its immense biodiversity, relies on the symbioses between cnidarians (e.g., scleractinian corals, octocorals, sea anemones, jellyfish) and multiple organisms including dinoflagellate algae (family Symbiodiniaceae), bivalves, crabs, shrimps, and fishes. In this review, we discuss the ramifications of whether coral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Such disruption could have been caused potentially by a strong fluctuation in temperature, as symbionts appear to be sensitive to increases in temperature (Corbin et al, 2017;Hurst et al, 2000;Sumi et al, 2017;van Opijnen & Breeuwer, 1999) and show the general geographical pattern of lower prevalence in warmer regions (Corbin et al, 2017). Moreover, experimental heat exposure was able to eliminate Wolbachia in twospotted spider mites (van Opijnen & Breeuwer, 1999), and a green stinkbug (Kikuchi et al, 2016) and symbiont reduction in response to increasing temperatures was found in coral reefs (Goulet & Goulet, 2021). Although the underlying reasons for admixed ancestry in some Kobe samples remain speculative, our findings suggest that environmental factors and associated changes in the bacterial community composition may have played a role.…”
Section: Interaction Between Bacterial Community Composition and Host...mentioning
confidence: 99%
“…Such disruption could have been caused potentially by a strong fluctuation in temperature, as symbionts appear to be sensitive to increases in temperature (Corbin et al, 2017;Hurst et al, 2000;Sumi et al, 2017;van Opijnen & Breeuwer, 1999) and show the general geographical pattern of lower prevalence in warmer regions (Corbin et al, 2017). Moreover, experimental heat exposure was able to eliminate Wolbachia in twospotted spider mites (van Opijnen & Breeuwer, 1999), and a green stinkbug (Kikuchi et al, 2016) and symbiont reduction in response to increasing temperatures was found in coral reefs (Goulet & Goulet, 2021). Although the underlying reasons for admixed ancestry in some Kobe samples remain speculative, our findings suggest that environmental factors and associated changes in the bacterial community composition may have played a role.…”
Section: Interaction Between Bacterial Community Composition and Host...mentioning
confidence: 99%
“…Symbiosis can facilitate physiological adaptation, as partner switching or ‘symbiont shuffling’ can provide mechanisms besides genetic evolution by which organisms can adapt to changing surroundings ( Cunning et al, 2015b ; Toby Kiers et al, 2010 ). Yet the interdependence between partners can also magnify the environmental sensitivities of mutualistic organisms, as both species must maintain function together under new conditions ( Apprill, 2020 ; Bénard et al, 2020 ; Goulet and Goulet, 2021 ). Therefore, we need to be precise in our understanding of when an abiotic stressor such as elevated temperature is affecting a host, its symbiont(s), both partners, or even modifying the dynamics of the interaction itself.…”
Section: Introductionmentioning
confidence: 99%
“…Across the world's coral reefs, biodiversity is supported by the mutualisms that exist between organisms such as corals or sea anemones, and their algal endosymbionts Symbiodiniaceae (Goulet and Goulet 2021). In addition to supporting diverse species assemblages through the creation of habitat and resources Chomicki et al 2019), these relationships also support secondary mutualisms, such as those between fishes and anemones (Fautin 1991).…”
Section: Introductionmentioning
confidence: 99%